2021
DOI: 10.1111/mec.16172
|View full text |Cite
|
Sign up to set email alerts
|

Host gene expression in wildlife disease: making sense of species‐level responses

Abstract: Recently emerged wildlife diseases that threaten population-or species-level persistence have forced conservation biologists to direct their attention toward disease processes, including transmission dynamics and host responses to pathogen exposure (Daszak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 149 publications
(185 reference statements)
0
1
0
Order By: Relevance
“…Patterns of higher immune gene expression in honeybees and stronger immune responses to pathogens were associated with increased wintering survival ( 63 ). However ( 64 ) showed that, on average, across several wildlife species (both invertebrates and vertebrates), less susceptible individuals had lower and more stable immune gene expression and sometimes better pathogen tolerance. It is possible that the decrease in immune gene expression with increasing tumor size in Tasmanian devils may also impair their ability to combat additional pathogens and parasites or additional immune stressors [but see ( 65 )].…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of higher immune gene expression in honeybees and stronger immune responses to pathogens were associated with increased wintering survival ( 63 ). However ( 64 ) showed that, on average, across several wildlife species (both invertebrates and vertebrates), less susceptible individuals had lower and more stable immune gene expression and sometimes better pathogen tolerance. It is possible that the decrease in immune gene expression with increasing tumor size in Tasmanian devils may also impair their ability to combat additional pathogens and parasites or additional immune stressors [but see ( 65 )].…”
Section: Discussionmentioning
confidence: 99%